Perbandingan Pandangan Pendidikan Dakwah Menurut KH. Hasyim Asy’ari dan Kh. Ahmad Dahlan - Wafi, Abdul (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study originates from the importance of understanding the philosophical foundations of da’wah education within the context of Indonesian Islam, which is rich in the thoughts of reformist scholars. Among them, KH. Hasyim Asy’ari and KH. Ahmad Dahlan represent two distinct yet complementary approaches—Islamic traditionalism and modernism. The purpose of this study is to compare their perspectives on da’wah education, including its objectives, methods, and underlying value orientations. The research employs a qualitative method with a library research approach, conducting a comparative analysis of the key works of both figures, such as Adabul ‘Alim wal Muta’allim and writings on the Muhammadiyah educational system. The findings reveal that KH. Hasyim Asy’ari emphasized da’wah grounded in moral exemplarity, ethics (adab), and the preservation of pesantren scholarly traditions, whereas KH. Ahmad Dahlan focused on socially engaged da’wah through modern education and community empowerment. Theoretically, this study enriches the discourse of Islamic education by proposing a synthesis between value-based education and action-based education. Practically, its findings can serve as a reference for developing a holistic model of da’wah education that integrates the spiritual, intellectual, and social dimensions in shaping a generation of Muslims who are both morally grounded and globally competitive.